2020
DOI: 10.3390/foods9020236
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Composition and Manufacturing Approach on the Physical and Rehydration Properties of Milk Protein Concentrate Powders

Abstract: This study investigated the physical and rehydration properties of milk protein concentrate (MPC) powders with five different protein contents (i.e., 38.9, 53.7, 63.6, 74.1, and 84.7%, w/w) prepared by recombining the ultrafiltration (UF) retentate and UF permeate of skim milk. Powder density and flowability increased, while the powder particle size decreased with decreasing powder protein content. The amount of non-wetting MPC powder decreased with decreasing protein content, demonstrating greater wettability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 43 publications
(72 reference statements)
3
18
0
1
Order By: Relevance
“…In MPC70 and MPC80, the particle movement and initial swelling due to water entry was much less noticeable than in the other MPCs. This is confirmed by other work looking at the same (Maidannyk et al, 2020) or similar (McSweeney et al, 2020) MPC powders, where the authors reported that MPC40-60 have a higher rate of water diffusion and wettability than higher protein powders. Moisture sorption is facilitated by hydrophilic lactose that acts as a channel for moisture transfer within the CM and as a spatial separator, disrupting the direct interaction of the hydrophobic ends of adjacent casein molecules (Baldwin, 2010;.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In MPC70 and MPC80, the particle movement and initial swelling due to water entry was much less noticeable than in the other MPCs. This is confirmed by other work looking at the same (Maidannyk et al, 2020) or similar (McSweeney et al, 2020) MPC powders, where the authors reported that MPC40-60 have a higher rate of water diffusion and wettability than higher protein powders. Moisture sorption is facilitated by hydrophilic lactose that acts as a channel for moisture transfer within the CM and as a spatial separator, disrupting the direct interaction of the hydrophobic ends of adjacent casein molecules (Baldwin, 2010;.…”
Section: Discussionsupporting
confidence: 79%
“…There is also evidence that milk fat can melt forming viscous liquid bridges (Peleg, 1977), however, this is unlikely to have occurred in our study (Foster, Bronlund & Paterson, 2005) because of the low temperature (5 o C) used in our experiments. MPC powder caking was confirmed (in the same powders as used in this study) by Maidannyk et al (2020), by an increase in particle size as found in MPC40 and MPC50 kept at RH >76 % at 21 ± 2°C. The same was observed in skim milk powder (SMP) but occurred at RH >54% (Murrieta-Pazos et al, 2011).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This fact indicated that the variation of whey composition (depending on the pH and the species) before drying was the main determining factor for the size distribution. Actually, it was demonstrated that a significant decrease in the particle size distribution of milk powder could be observed as a result of the decrease of the protein content and the increase of the ash quantity (McSweeney, Maidannyk, Montgomery, O'Mahony, & McCarthy, 2020). This fact may explain the variation in the size distribution between acidic or sweet camel and bovine whey powders.…”
Section: Bulk Composition and Size Distributionmentioning
confidence: 99%